Frequency and source of worries in an International sample of pregnant and postpartum women during the Covid-19 pandemic - Diego F. Wyszynski; Sonia Hernandez-Diaz; Vanessa Gordon-Dseagu; Noemi Ramiro; Archana Basu; Hannah H. Kim; Karestan C. Koenen (BMC, 2021)
Abstract Background Pregnant and postpartum women face unique challenges and concerns during the COVID-19 pandemic. Thus far, no studies have explored the factors associated with increased levels of worry in this population globally. The current study sought to assess the frequency and sources of worry during the COVID-19 pandemic in an international sample of pregnant and postpartum women. Methods We conducted an anonymous, online, cross-sectional survey in 64 countries between May and June 2020. The survey was available in 12 languages and hosted on the Pregistry platform for COVID-19 studies. Participants were sought mainly on social media platforms and online parenting forums. The survey included questions related to demographics, level of worry, support, stress, COVID-19 exposure, frequency of media usage, and mental health indicators. Results The study included 7561 participants. Eighty-three percent of all participants indicated that they were either 'somewhat' or 'very' worried. Women 13-28 weeks pregnant were significantly more likely to indicate that they were 'very worried' compared to those who were postpartum or at other stages of pregnancy. When compared with women living in Europe, those in Africa, Asia and Pacific, North America and South/Latin America were more likely to have increased levels of worry, as were those who more frequently interacted with social media. Different forms of support and stress also had an impact upon level of worry, while indicators of stress and anxiety were positively associated with worry level. Conclusion Pregnant and postpartum women are vulnerable to the changes in societal norms brought about by the COVID-19 pandemic. Understanding the factors associated with levels of worry within this population will enable society to address potential unmet needs and improve the current and future mental health of parents and children.